Are Malaysian Islamic banks' corporate social responsibilities effective? A stakeholders' view. Issue 1 (5th February 2018) - Jaiyeoba, Haruna Babatunde; Adewale, Abideen Adeyemi; Quadry, Mahmud Oluwaseyi
Abstract : Purpose: The purpose of this paper is to investigate the effectiveness of Islamic banks' corporate social responsibility (CSR) using data collected from stakeholders in Malaysia. While Islamic scholars have developed the Islamic CSR from the Qur'anic verses, the Sunnah of the Prophet (SAW) and from the western ideologies, the focus of this paper is to assess the effectiveness of the developed Islamic CSR practices. Design/methodology/approach: Quantitative research design was adopted for this study. Exploratory factor analysis, confirmatory factor analysis, and other analyses are performed on the data collected from 193 stakeholders in Malaysia. Findings: Based on the data collected and analyzed, the results show that stakeholders view the Malaysian Islamic banks' CSRs as effective. Research limitations/implications: This study investigates the effectiveness of Malaysian Islamic banks' CSR based on the survey data collected. However, future studies could explore this in greater depth using mixed methods. Practical implications: The research findings have great implications for researchers. Since this study is among the few research studies that investigate the effectiveness of Islamic CSR, the researchers have paved ways for further investigation in this area. In addition, the study encourages the Malaysian Islamic banks and other Islamic financial institutions to contribute more to the society. Originality/value: The study examines the effectiveness of Islamic banks' CSR and contributes to the growing discussions on the Islamic CSR. The study has opened up this area for further investigations by other researchers.